Tomato Spotted Wilt Virus Particle Morphogenesis in Plant Cells - Kikkert, Marjolein (American Society for Microbiology, 1999)
A model for the maturation of tomato spotted wilt virus (TSWV) particles is proposed, mainly based on results with a protoplast infection system, in which the chronology of different maturation events could be determined. By using specific monoclonal and polyclonal antisera in immunofluorescence and electron microscopy, the site of TSWV particle morphogenesis was determined to be the Golgi system. The viral glycoproteins G1 and G2 accumulate in the Golgi prior to a process of wrapping, by which the viral nucleocapsids obtain a double membrane. In a later stage of the maturation, these doubly enveloped particles fuse to each other and to the endoplasmic reticulum to form singly enveloped particles clustered in membranes. Similarities and differences between the maturation of animal-infecting (bunya)viruses and plant-infecting tospoviruses are discussed.